2021
DOI: 10.3389/fmed.2021.699921
|View full text |Cite
|
Sign up to set email alerts
|

Proprioceptive Training for Knee Osteoarthritis: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Background: There is increased interest in proprioceptive training for knee osteoarthritis (KOA). However, little consensus supports the effectiveness of this intervention.Objective: This meta-analysis aimed to assess the effects of proprioceptive training on symptoms, function, and proprioception in people with KOA.Methods: The PubMed, Cochrane Library, Web of Science, and EMBASE databases were systematically searched from the inception dates to April 16, 2021 for relevant randomized controlled trials (RCTs).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 67 publications
0
10
0
4
Order By: Relevance
“…For knee OA, four SRs and five additional RCTs were identified on the exercise26–28 modalities Tai Chi, yoga, stationary cycling, proprioceptive training, weight-bearing and non-weight bearing exercise, and neuromuscular exercise combined with strength training 29–33. Overall, the results showed small to moderate positive effects on pain and function for all these exercise modalities compared with no-exercise control (no intervention, waiting list or non-exercise interventions).…”
Section: Resultsmentioning
confidence: 99%
“…For knee OA, four SRs and five additional RCTs were identified on the exercise26–28 modalities Tai Chi, yoga, stationary cycling, proprioceptive training, weight-bearing and non-weight bearing exercise, and neuromuscular exercise combined with strength training 29–33. Overall, the results showed small to moderate positive effects on pain and function for all these exercise modalities compared with no-exercise control (no intervention, waiting list or non-exercise interventions).…”
Section: Resultsmentioning
confidence: 99%
“…Another study comparing sensorimotor and functional training after TKA found greater improvements in JPS in the sensorimotor group at bilateral extremities [22]. Therefore, these authors recommend SMT incorporating rehabilitation as being clinically effective [7,22,46].…”
Section: Discussionmentioning
confidence: 98%
“…A recent meta-analysis showed that proprioceptive training is more effective than nonproprioceptive training in improving pain, stiffness, function, muscle strength, and JPS in patients with OA [46]. In addition, sensorimotor home-based exercises have been proven to restore neuromuscular activation and muscle strength [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, there is evidence to suggest that abnormal foot posture, combined with the onset of KOA, can affect force distribution across the entire lower limb and potentially affect the alignment of the knee joint [39,40]. Therefore, comprehensive foot posture assessment is important to understand the development of KOA and to contribute to the selection of the appropriate intervention method [9]. Several studies have reported a more pronated foot posture in patients with KOA [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…In people with KOA, activities such as climbing stairs, walking, climbing become difficult over time with poor balance, restriction in range of motion, deformities, damage to joint mechanoreceptors and increased pain [8]. Since proprioception originates from proprioceptors in skeletal muscles, tendons, ligaments and joint capsule, a decrease in proprioceptive sensation can be seen with the progression of KOA, and a decrease in proprioception may be a cause of increased knee pain or activity limitation [9][10][11][12]. There are studies showing significantly higher pain scores, lower quality of life scores, and decreased knee proprioception in KOA compared to healthy individuals [13,14].…”
Section: Introductionmentioning
confidence: 99%